Refashioning pop music in Asia : cosmopolitan flows, political tempos, and aesthetic industries - Chun, Allen John Uck Lun, 1952-; Rossiter, Ned; Shoesmith, Brian (ConsumAsiaN book series (Richmond, England), 2004)
This collection of thirteen essays examines cultural, political, economic, technological and institutional aspects of popular music across Asia, from India to Japan.